Distribution, modes of occurrence, and main factors influencing lead enrichment in Chinese coals - Kunqi Lin; Wenhui Huang; Robert B. Finkelman; Jing Chen; Shuo Yi; Xiaonan Cui; Yuanzheng Wang (International Journal of Coal Science & Technology, 2020)
Abstract Lead is a potentially harmful element that has caused serious environmental pollution during its mining and use along with serious human health problems. This study assessed lead in Chinese coals based on published literature, with a particular focus on data reported since 2004. The analysis included 9447 individual samples from 103 coalfields or mines in 28 provinces in China. The arithmetic mean content of lead in the studied coals was 15.0 μg/g. Considering the coal reserves, the weighted-average lead concentration in Chinese coals was calculated to be 19.6 μg/g. Lead was significantly enriched in the coals from Henan Province and enriched in the coals from the Tibet Autonomous Region. The coals from Tibet–Western Yunnan and the southern areas of China had elevated lead concentrations. Sulfides are the primary hosts of lead in Chinese coals, although other hosts include silicates, organic matter, carbonates, and other minerals. Source rocks in the sediment-source region and marine environments may be the most significant factors contributing to lead enrichment in Chinese coals. Hydrothermal fluids and peat-forming plants also contribute to lead enrichment in some Chinese coals.